2021
DOI: 10.37939/jrmc.v25i2.1507
|View full text |Cite
|
Sign up to set email alerts
|

To determine the rate of success of external cephalic version in low risk breech presentations and possible factors affecting its success in POF hospital, Wah Cantt.

Abstract: Abstract   Background The caesarean section rate  is on the rise for various reasons. One of the reason is breech presentation . External cephalic version is a procedure to manipulate the baby from breech to cephalic presentation externally through the maternal abdomen under USG guidance . Success in ECV decreases the breech presentation and  hence caesarean section rate . Methods This retrospective study was conducted by Wah Medical College in POF hospital from10 Oct 2015- 10 Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Cochrane Central and clinicaltrials.gov provided only a few additional records. During citation searching, we found further potentially relevant articles(e.g., 53 . We later realized that they could be found in Google Scholar, but none of those other databases, likely because they were published in lesser-known international journals.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…Cochrane Central and clinicaltrials.gov provided only a few additional records. During citation searching, we found further potentially relevant articles(e.g., 53 . We later realized that they could be found in Google Scholar, but none of those other databases, likely because they were published in lesser-known international journals.…”
Section: Consent For Publicationmentioning
confidence: 99%
“…8 In our recently published study, we found multiparity unengaged breech & complete flexed breech as predictors of successful ECV, and the success rate of ECV was 48.2% in the study. 9 There are few contraindications for ECV, like placenta previa, placental abruption, abnormal CTG/doppler, severe preclampsia & conditions where the indication for caesarean section is already present. The complication rate of ECV procedure is very low, only a 0.5% rate of emergency caesarean within 24 hrs is narrated due to abnormal CTG or vaginal bleeding.…”
Section: Introductionmentioning
confidence: 99%